PENGARUH KEMAMPUAN MANAJERIAL, KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI KERJA TERHADAP KINERJA GURU PAUD DI KECAMATAN CISEENG - Winda Nurbaya; Ersam Mahendrawan; Lili Nurlaili (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the influence of managerial ability, transformational leadership, and work motivation on the performance of PAUD teachers in Ciseeng District. This study uses a quantitative approach with a correlational method. The study population was 167 non-formal PAUD teachers, with a sample of 118 respondents determined using the Slovin formula. Data were collected through a closed-ended questionnaire based on a Likert scale that has been tested for validity and reliability. Data analysis was carried out through descriptive statistics, prerequisite tests, simple linear regression, multiple linear regression, partial tests, simultaneous tests, and coefficients of determination. The results showed that managerial ability had a positive and significant effect on PAUD teacher performance with a t-value of 5.928 and a significance of 0.000. Transformational leadership had a positive and significant effect with a t-value of 4.194 and a significance of 0.000. Work motivation also had a positive and significant effect with a t-value of 1.982 and a significance of 0.043. Simultaneously, the three variables had a significant effect on PAUD teacher performance with an F-value of 33.631 and a significance of 0.000. The coefficient of determination of 0.470 indicates that these three variables explain 47% of the variation in teacher performance, while 53% is influenced by factors outside the study. This finding suggests that improving early childhood education (PAUD) teacher performance requires strengthening institutional governance, inspiring and change-oriented leadership, and sustainable work motivation. The synergy of these three factors is a strategic aspect in improving the quality of early childhood education services in Ciseeng District.